Soybean root hairs: A valuable system to investigate plant biology at the cellular level - Libault, Marc (Plant Signal Behav, 2010)
Plant organs and tissues are composed of many differentiated cell types. Most functional genomic studies sample whole tissues, which dilutes the signals that may arise from individual cells within the population. The result is an averaging of the cellular response. In order to overcome these issues of ‘signal dilution’, methods are needed to allow the full application of modern functional genomics tools to the study of a single differentiated plant cell type. In order to address this need, we developed a method for the isolation of soybean root hair cells, a single epidermal cell type, in sufficient quantities and purity to perform a variety of functional genomic analyses. As a first demonstration of the potential of soybean root hair cells to study plant systems biology, we compared the root hair transcriptome and proteome.